Languages in contact:: European Portuguese meets Austrian German - Fernandes, Cláudia (Todas as Letras - Revista de Língua e Literatura, 2016)
Migrant communities are the perfect stage to observe languages in contact. Austria has a small and recent Portuguese community and this fact allowed us to analyze the behavior of European Portuguese in a German spea- king context. Interferences are likely to happen, but are the speakers aware of these? Do they really command their languages separately? What are the stra-tegies they refer to? These and other answers can be found with the present investigation.